Producción y calidad forrajera de Brachiaria humidicola en monocultivo y en asocio con Acacia mangium en un suelo ácido en el Trópico Húmedo - Bolívar, Diana (1999)
This study was conducted at the IDIAP experimental station of Calabacito, Panama (mean annual rainfall of 2500 mm and temperature 27 °C; soils are acid with high Al saturation), to determine the effect of the timber tree Acacia mangium on the productivity and quality of Brachiaria humidicola pastures. The treatments were: 1) B. humidicola monoculture; and 2) B. humidicola in mixture with A. mangium. The forage had significantly lower crude protein concentration (32 vs 46 g kg exponente -1) and solubility (52 vs 58 percent) in the monoculture vs the mixture, respectively. Mean total forage yields of the mixture was 28 percent higher than the monoculture. In the dry season, dead pasture biomass represented 60 percent of total dry matter measured in the grass monoculture whereas it was only 30 percent for the mixture. The leaf: stem ratio of B. humidicola was higher for the mixture. It is concluded that the integration of A. mangium in silvopastoral systems with B. humidicola contributed to increased pasture yield of higher nutritive value.